The dose-response relationship between interval-training and VO2max in well-trained endurance runners: A systematic review - Parmar, A.; Jones, T. W.; Hayes, P. R. (Journal of Sports Sciences, 2021)
Success in endurance running is primarily determined by maximal aerobic power (VO2max), fractional utilization, and running economy (RE). Within the literature, two training modalities have been identified to improve VO2max; continuous training (CT) and interval-training (IT). The efficacy of IT to improve VO2max in well-trained runners remains equivocal, as does whether a dose-response relationship exists between the IT training load performed and changes in VO2max. A keyword search was performed in five electronic databases. Seven studies met the inclusion criteria for this systematic review. The training impulse (TRIMP) was calculated to analyse relationships between training load and changes in VO2max, by calculating the time accumulated in certain intensity domains throughout a training intervention. Non-significant (P>0.05) improvements in VO2max were reported in six studies, with only one study reporting a significant (P<0.05) improvement following the IT interventions. A relationship between the training session impulse of the interval-training performed (IT STRIMP) and VO2max improvements were observed. The efficacy of IT to improve VO2max in well-trained runners remains equivocal, nevertheless, the novel method of training-load analysis demonstrates a relationship between the IT STRIMP and VO2max improvements. This provides practical application for the periodization of IT within the training regime of well-trained distance runners.